Systemic risk in the Danish interbank netting system - Morten L. Bech; Bo Madsen; Lone Natorp (Danmarks Nationalbank, 2002)
Central banks have become increasingly worried about systemic risks to the financial market and infrastructure stemming from payment systems. Failure to settle by a participant in a netting system can potentially jeopardize the settlement of other participants. The fear of a systemic crisis has been one of the primary motivations for the introduction of Real Time Gross Settlement systems around the world. This paper provides an assessment of the systemic risk inherent in the Danish interbank netting system. In accordance with similar empirical studies conducted in other European countries, the risk is found to be low.
Keywords: 330; payment system; systemic risk; netting; Zahlungsverkehr; Bankrisiko; Theorie